2013
DOI: 10.1177/1550059413490930
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Aphasic Status Epilepticus as Initial Presentation of Nonketotic Hyperglycemia

Abstract: Diagnosis of aphasic status epilepticus is sometimes not easy because of its rarity and electroclinical dissociation. Although most cases are associated with organic brain lesions, nonketotic hyperglycemia (NKH)-related aphasic status epilepticus is rare, especially if it is isolated (without other clinical seizure activity). On the other hand, unlike other metabolic disorders, or hypoglycemia-related generalized seizures, focal motor seizure and epilepsia partialis continua can occur in 25% of NKH, with seizu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 13 publications
4
14
0
Order By: Relevance
“…NKHrelated ASE seems to have its initial presentation as a mixed aphasia [12], similar to our case. This kind of aphasia is similar to that of patients with isolated aphasia, making it more difficult to establish an accurate diagnosis of NKH-related ASE, because of being very rare.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…NKHrelated ASE seems to have its initial presentation as a mixed aphasia [12], similar to our case. This kind of aphasia is similar to that of patients with isolated aphasia, making it more difficult to establish an accurate diagnosis of NKH-related ASE, because of being very rare.…”
Section: Discussionsupporting
confidence: 68%
“…On literature review, initial status epilepticus presenting with aphasia has been reported in multiple sclerosis [10], diabetes [11], NKH [3,12], and AIDS-toxoplasmosis complex [13] or induced by the cephalosporin cefepime [14]. NKHrelated ASE seems to have its initial presentation as a mixed aphasia [12], similar to our case.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…These conditions could more or less be excluded by normal spinal tap, and resolving aphasia under anticonvulsant therapy may support ictal origin. De novo status epilepticus presenting with aphasia has been reported in multiple sclerosis [11,12], diabetes [13], nonketotic hyperglycemia [14,15], and AIDS-toxoplasmosis complex [16] or induced by the cephalosporine cefepime [17]; these conditions could also be excluded.…”
Section: Discussionmentioning
confidence: 97%
“…Finally, even though the possibility of seizures with purely ''negative'' clinical symptomatology remains highly controversial, there are in the literature some very rare descriptions of long-lasting motor or language neurological deficits considered to be related to partial status epilepticus [28,71,110,165]. Of course, EEG in these situations would in fact represent the key to the diagnosis.…”
Section: Focal Neurological Deficitsmentioning
confidence: 94%